Management of Radicular Cyst of Maxillary Anterior Region by Using Titanium-Prepared Platelet-Rich Fibrin (T-PRF): A Case Report (International Journal of Food and Nutritional Sciences, 2022)
Radicular cysts are the most common inflammatory cysts found in the jaws. In order to promote bone regeneration and periapical tissue healing, surgical intervention seeks to eradicate periapical disease. With the new idea of rapid healing, autologous platelet rich fibrin is a healing biomaterial for oral surgical abnormalities. Third-generation platelet concentrate, titanium-prepared platelet rich fibrin (T-PRF), was created to counteract the negative effects of silica in glass tubes and has a longer rate of resorption. This case report's objective is to demonstrate the results of T-PRF applied to the bone defect that develops following the radicular cyst's enucleation. Following up for six months, there was a noticeable increase in bone density. Treatment of bone abnormalities with T-PRF has demonstrated efficacy. Consequently, it is believed that it can be applied as a regenerative material to cure bone abnormalities.